Handbook of Face Recognition - Li, Stan Z.; Li, Stan Z.; Jain, Anil K.; Jain, Anil K. (Springer London : Imprint: Springer, 2011)
The history of computer-aided face recognition dates back to the 1960s, yet the problem of automatic face recognition – a task that humans perform routinely and effortlessly in our daily lives – still poses great challenges, especially in unconstrained conditions. This highly anticipated new edition of the Handbook of Face Recognition provides a comprehensive account of face recognition research and technology, spanning the full range of topics needed for designing operational face recognition systems. After a thorough introductory chapter, each of the following 26 chapters focus on a specific topic, reviewing background information, up-to-date techniques, and recent results, as well as offering challenges and future directions. Topics and features: Fully updated, revised and expanded, covering the entire spectrum of concepts, methods, and algorithms for automated face detection and recognition systems Examines the design of accurate, reliable, and secure face recognition systems Provides comprehensive coverage of face detection, tracking, alignment, feature extraction, and recognition technologies, and issues in evaluation, systems, security, and applications Contains numerous step-by-step algorithms Describes a broad range of applications from person verification, surveillance, and security, to entertainment Presents contributions from an international selection of preeminent experts Integrates numerous supporting graphs, tables, charts, and performance data This practical and authoritative reference is the essential resource for researchers, professionals and students involved in image processing, computer vision, biometrics, security, Internet, mobile devices, human-computer interface, E-services, computer graphics and animation, and the computer game industry. Dr. Stan Z. Li is Professor at the National Laboratory of Pattern Recognition, Director of the Center for Biometrics and Security Research, and Director of the R&D Center for Visual Internet of Things, within the Chinese Academy of Sciences. Dr. Anil K. Jain is University Distinguished Professor in the Department of Computer Science and Engineering at Michigan State University, U.S.A.